The cost of collateralized borrowing in the Colombian money market: Does connectedness matter? - Martínez, Constanza; León, Carlos (Journal of Financial Stability, 2016)
We estimate two standard spatial econometric models in order to study the cost of collateralized borrowing among Colombian financial institutions, and its relationship with traditional determinants (leverage, size, and borrowing concentration), and with the observed linkages among financial institutions (spatial variables). Our main findings indicate that (i) the selected models are able to capture the extent and significance to which linkages matter for money market's liquidity pricing in the form of a spatial dependence parameter; (ii) spatial effects play a significant role in the pricing of liquidity in the collateralized money market; (iii) direct and spill-over effects from financial institutions’ size and the spatially lagged value of financial leverage and borrowing concentration most significantly determine the cost of collateralized borrowing; (iv) traditional determinants are of low explanatory power by themselves. Concurrent with contemporary lending relationships literature, our results emphasize the importance of connectedness among financial institutions, and are essential in the context of a macro-prudential perspective of financial stability and systemic risk.